Einkommensteuertarife in der Bundesrepublik Deutschland und ihre Folgen für die Belastung ausgewählter Haushaltstypen - Alfred Boss; Hans Christian Müller; Axel Schrinner (Kiel Institute for the World Economy (IfW), 2013)
Facing the general election in 2013, the level of the income tax is a major issue of the economic policy debate in Germany. The paper presents data on the income tax burden in the period 1958-2012. The data refer to specific levels of real income as well as to specific levels of income in relation to the income on average. It turns out that the discretionary changes of the income tax rates since 1958 did not suffice to avoid an increase of the marginal tax rates for typical taxpayers. As to the average tax rates, the picture is a bit different; low income earners realized a small decrease of their tax rates if their real income did not rise.
Keywords: H30; 330; marginal income tax rates in Germany; bracket creep; incentives to work